High precision MI sensor with low energy consumption driven by low-frequency Wiegand pulse - Ruixuan Yao; Yasushi Takemura; Tsuyoshi Uchiyama (AIP Advances, 2023)
This study introduces a new method to drive high-precision magneto-impedance (MI) sensors with low power consumption using a Wiegand sensor to replace the oscillator circuits of the MI sensor. We studied the characteristics of an MI sensor driven by low-frequency pulses and concluded that pulses with a fast rise time and small excitation current are necessary to induce a significant MI effect. The Wiegand sensor induced 10 Hz low-frequency pulse voltages of approximately 12 V and a constant width of 20 μs when an alternating magnetic field of 5 mT/μ0 alternating magnetic field was applied. A fast rise-time-shaping circuit was designed to shape the Wiegand pulses with a fixed amplitude and rise time of less than 100 ns. The MI sensor exhibited a good output linearity of 0.04 mV/μ0T for detecting magnetic field in the range of ±150 μT when Wiegand pulses of amplitude 1 V were supplied. The power consumption of the MI sensor was reduced from milliwatts (mW) to microwatts (μW) and its usage time was extended by 300% compared to that of the previous design. This newly designed MI sensor is suitable for use in bio-magnetic field measurements, constant vehicle detection devices, and other applications.